(untitled) (Heritage, 2025)
The article analyzed the role of emotions—fear, love, and sorrow—in the second version of Ljubomir Simović’s play The Battle of Kosovo using a literary-emotionological approach. As the Kosovo legend, with its tragic and eschatological potential, became central to Serbian historical drama, particularly in the 20th century, the work explored Simović’s integration of collective heritage with his artistic vision. The methodological framework incorporated affective narratology, psychology, and emotionology to examine the dramatic narrative structure and to enable an affective reading of the text. The first section focused on fear as a central emotion, exploring its role in character development and innovations compared to the traditional Kosovo legend. Simović emphasizes fear to reflect human nature. Characters like the washerwoman Pralja and healer Bogoje express fear of loss, while Prince Lazar and Princess Milica convey concerns for Serbia’s future and their families.Simović also highlights fear among the Turks, particularly over betrayal by Serbian vassals. Fear emerges as both a motivator of heroism and a source of moral weakness. The second section examined love’s stylization. Although overshadowed by hatred and discord, love appears in distorted forms such as ambition and greed. Simović contrasts this with the noble love of Kosovo heroes, evident in lyrical songs blending patriotism and Christian sacrifice. The final section analyzed sorrow, prevalent in Serbian oral tradition and medieval literature. Simović dramatizes this emotion through warriors’ farewells and a soldier’s lament, capturing grief and the trauma of survivors. This modernizes the Kosovo narrative, emphasizing the universal human cost of war and the heroism of sacrifice.